Alcoholic liver disease - Lucey, Michael (Henry Stewart Talks, 2011)
Alcoholism, including the toll of alcoholism, is key to understanding alcoholic liver disease (ALD), Alcoholism is clandestine disorder, Abstinence is key to recovery from both alcoholism and ALD, There are few evidence-based therapies for ALD, other than abstinence, Liver transplantation is valuable in selected subjects with ALD